Improving the quality of service delivery as a strategy to reduce maternal and perinatal mortality. - Távara, Luis (2015)
OBJETIVE: To examine the results of a strategy to improve quality of services in the reduction of maternal and perinatal mortality. DESIGN: Operational research whose baseline a set of indicators taken into selected health facilities in 1996 and after a series of interventions were again measured in 1999. The selected establishments were 13 hospitals and 24 heads of service network in the regions of Lima -Callao, Cajamarca, Loreto and Apurimac. In each of the Ten Steps for Safe Childbirth Initiative was introduced in order to help improve the quality and warmth of institutional delivery and thus help reduce maternal and perinatal mortality. RESULTS: Up to September 1999 the initiative was adequately developed in 12 hospitals and 16 headends. 100% of establishments adopted an explicit policy for safe motherhood, allowing train 4,497 health workers. All establishments have managed to form community support groups. Perinatal information system, partografía alert curvy, postpartum contraception and abortion: Joined appropriate technologies. mother kangaroo, outpatient care for incomplete abortion and waiting house. The number of pregnant women for prenatal care increased by 14%, being more noticeable in the provinces, where it averaged 33% increase. The concentration of 4 or more prenatal visits also increased by 41% and institutional deliveries increased by 9.24%. having reached a figure of 27% inside. The blood bank operation increased from 42% to 92% and epidemiological surveillance was established in 100% of the establishments. The user satisfaction reached to 89.5%. The maternal mortality rate fell 70 points on average, still higher inside while the perinatal mortality rate dropped 5 points. CONCLUSION: Ten Steps for Safe Childbirth Initiative is a good strategy to contribute to the reduction of maternal and perinatal mortality.